Negativni spolni stereotipi in predsodki v slovenski družbeno-religijski sferi - Furlan, Nadja (Monitor ISH, 2008)
Given the contemporary tendencies towards gender equality, the question of gender stereotypes and prejudices is a topical issue. The traditional stereotyped images of men and women are changing and gaining new contents. To enable in-depth investigation into the gender stereotypes and prejudices underlining the discrimination of women in Slovene society and the Catholic Church, a small-scale study has been conducted with the help of a questionnaire. The research findings reveal a residue of negative stereotypes and the accompanying discrimination, but also a more optimistic trend towards equality.
Keywords: družba; society; spolna diskriminacija; stereotipi; predsodki; tradicionalnost; vloge; Slovenia; Slovenija; raziskave